2010
DOI: 10.1016/j.physb.2009.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Premelting of Al nonperfect (111) surface

Abstract: Melting behaviors of aluminum (111) perfect/nonperfect surfaces, characterized by structure ordering parameter, have been investigated by classical molecular dynamics simulation with embedded atom method potential. Al (111) perfect surface has a superheating temperature above bulk Al melting point T m , in this work, by about 80 K.Al nonperfect (111) surface has somewhat different local lattice structure from that on (111) perfect surface. Al nonperfect (111) surfaces tempt to premelt when temperature is less … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
1
4
0
1
Order By: Relevance
“…Moreover, the range of surface energies at (0 0 1), (1 1 0) and (1 1 1) with respect to the uncertainties of single vacancy formation energy are predicted to be (0.76, 0.87), (0.98, 1.12) and (0.68, 0.78) J m −2 , respectively (see figure 13). Values of the three surface energies calculated by density functional theory [48,63] are 0.84, 0.91 and 0.75 J m −2 , respectively, while the experimental value is 0.98 J m −2 averaged over different surfaces [64]. This indicates that our predicted ranges of the surface energies agree well with the results of density functional theory and also experimental values.…”
Section: Sensitivity Of Extrapolated Results Of Potentials To the Ref...supporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, the range of surface energies at (0 0 1), (1 1 0) and (1 1 1) with respect to the uncertainties of single vacancy formation energy are predicted to be (0.76, 0.87), (0.98, 1.12) and (0.68, 0.78) J m −2 , respectively (see figure 13). Values of the three surface energies calculated by density functional theory [48,63] are 0.84, 0.91 and 0.75 J m −2 , respectively, while the experimental value is 0.98 J m −2 averaged over different surfaces [64]. This indicates that our predicted ranges of the surface energies agree well with the results of density functional theory and also experimental values.…”
Section: Sensitivity Of Extrapolated Results Of Potentials To the Ref...supporting
confidence: 79%
“…13). Values of the three surface energies calculated by density functional theory [48,63] are 0.84, 0.91 and 0.75 J/m 2 , respectively, while the experimental results are an averaged result of 0.98 J/m 2 over difference surfaces. This indicates that our predicted ranges of the surface energies agree well with the results of density functional theory or experiments.…”
Section: Sensitivity Of Extrapolated Results Of Potentials To the mentioning
confidence: 94%
“…Zou et al [81] employed VG to analyze the daily and monthly sunspot series and got some new insights. Tang et al [82] constructed and analyzed complex networks from traffic time series and indicated that complex network is a practical tool for exploring dynamics in traffic time series. Banerjee et al [83] presented a fresh and broad yet simple approach towards information retrieval in general and diagnostics in particular by applying the theory of complex networks on multidimensional, dynamic images.…”
mentioning
confidence: 99%
“…The surface melting behaviors of macro-crystals for Al, Cu and Ag have been investigated by several researchers. 21–50 For surface melting of the Al macro-crystal (110) surface, Stoltze et al 21 applied the molecular dynamics (MD) simulations to obtain the start melting temperature and the thickness of the disordered layer, which was confirmed by Gon et al , 22,24 Dosch et al 23 and Pavlovska et al 25 Then the surface melting together with the thickness of the quasi-liquid layer on Al(110) was observed by Theis and Horn. 28 The Monte Carlo (MC) simulation employed by Cox et al 31 indicated that Al(110) would melt approximately 200 K below the bulk melting temperature.…”
Section: Introductionmentioning
confidence: 86%